1999
DOI: 10.1016/s1074-7613(00)80064-3
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 10–Mediated Immunosuppression by a Variant CD4 T Cell Epitope of Plasmodium falciparum

Abstract: The immunodominant CD4 T cell epitope region, Th2R, of the circumsporozoite protein of Plasmodium falciparum is highly polymorphic. Such variation might be utilized by the parasite to escape from or interfere with CD4 T cell effector functions. Here, we show that costimulation with naturally occurring altered peptide ligands (APL) can induce a rapid change from IFNgamma production to the immunosuppressive mediator interleukin 10 (IL-10). This mechanism may contribute to the low levels of T cell responses obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
1
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 59 publications
1
110
1
4
Order By: Relevance
“…By contrast, IL-10 might limit inflammation in the vicinity of spz invasion. IL-10 inhibits some T cell responses to P. falciparum Ag [31], but IL-10 also accompanies protective immunity in malaria endemic areas [32]. Hence, it is possible that the inflammatory and regulatory cytokines are coordinately induced during protection against malaria.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, IL-10 might limit inflammation in the vicinity of spz invasion. IL-10 inhibits some T cell responses to P. falciparum Ag [31], but IL-10 also accompanies protective immunity in malaria endemic areas [32]. Hence, it is possible that the inflammatory and regulatory cytokines are coordinately induced during protection against malaria.…”
Section: Discussionmentioning
confidence: 99%
“…1 Evidence for its immunosuppressive activity has been based on the observations that (i) increased production of IL-10 ex vivo and in animal models was associated with states of immunosuppression, 2,3 (ii) neutralizing antibodies to IL-10 reversed hyporesponsiveness of T cells ex vivo, 4,5 and (iii) deletion of the IL-10 gene rendered mice more resistant to tumors or infection and more susceptible to infection pathology or autoimmune disease. [6][7][8][9] Substantial interindividual variability has been noted in several studies with humans, and heritability of high or low IL-10 secretion was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Out of these peptides pairs only one pair (M5/M6) reflected the MAD20 allelic prevalence with reactivity of 65% and 35% in Gambian donors, respectively [16]. Reactivity to M3/M4 was equally distributed amongst donors, while [20,21]. Index peptide was pre-pulsed first at 30 lg/mL onto PBMC and the other variant 1 h later at the peptide concentrations indicated (10-90 lg/mL).…”
Section: Allelic Immune Interference Of Msp-1-specific Ifn-c Responsementioning
confidence: 99%
“…One possible explanation for the unexpected allelic T cell reactivity pattern to M3/4 and M7/8 was that some of the reactivity to these epitopes was being suppressed. In pre-erythrocytic malaria, CS protein variants can turn off some types of T cell responses to each other by APL antagonism and through immune interference with the stimulation of T cell responses in PBMC cultures [10,20,21]. We thus investigated whether a similar mechanism is involved in the case of allelic MSP-1 variants in malaria-exposed donors.…”
Section: Allelic Immune Interference Of Msp-1-specific Ifn-c Responsementioning
confidence: 99%
See 1 more Smart Citation